Altered perception‐action binding modulates inhibitory control in Gilles de la Tourette syndrome. (20th June 2018) - Petruo, Vanessa; Bodmer, Benjamin; Brandt, Valerie C.; Baumung, Leoni; Roessner, Veit; Münchau, Alexander; Beste, Christian
Abstract : Background: Gilles de la Tourette Syndrome (GTS) is a multifaceted neuropsychiatric developmental disorder with onset in childhood or adolescence and frequent remissions in early adulthood. A rather new emerging concept of this syndrome suggests that it is a disorder of purposeful actions, in which sensory processes and their relation to motor responses (actions) play a particularly important role. Thus, this syndrome might be conceived as a condition of altered 'perception‐action binding'. In the current study, we test this novel concept in the context of inhibitory control. Methods: We examined N = 35 adolescent GTS patients and N = 39 healthy controls in a Go/Nogo‐task manipulating the complexity of sensory information triggering identical actions; i.e. to inhibit a motor response. This was combined with event‐related potential recordings, EEG data decomposition and source localization. Results: GTS patients showed worse performance compared to controls and larger performance differences when inhibitory control had to be exerted using unimodal visual compared to bimodal auditory‐visual stimuli. This suggests increased binding between bimodal stimuli and responses leading to increased costs of switching between responses instructed by bimodal and those instructed by unimodal stimuli. The neurophysiological data showed that this was related to mechanisms mediating between stimulus evaluation and response selection; i.e. perception‐action binding processes in the right inferior parietal cortex (BA40). Conclusions: Stimulus‐action inhibition binding is stronger in GTS patients than healthy controls and affects inhibitory control corroborating the concept suggesting that GTS might be a condition of altered perception‐action integration (binding); i.e. a disorder of purposeful actions.